The experiences, views, and needs of health professionals who provide care to adults on the autism spectrum. Issue 2 (2nd July 2020) - Urbanowicz, Anna; Parkin, Timothy; van Dooren, Kate; Girdler, Sonya; Ciccarelli, Marina; Lennox, Nick
Abstract: Health professionals are in a unique position to influence the health outcomes and healthcare experiences of adults on the autism spectrum. The aim of this research was to describe the experiences, views, and needs of health professionals providing care to adults on the spectrum. 78 health professionals, 42 from disability-specific or autism-specific settings, across Australia completed an online survey about providing health care to adults on the autism spectrum. About two-thirds of the health professionals strongly agreed or agreed that they felt knowledgeable (63%) and strongly agreed or agreed that they felt competent (62%) in providing care to this population. Fifty-nine percent strongly agreed or agreed that they felt confident in providing care to adults on the autism spectrum. A higher proportion of health professionals working in disability-specific or autism-specific settings strongly agreed or agreed to feeling competent, knowledgeable, or confident, or any combination of these three variables, providing care to adults on the autism spectrum in comparison to professionals not working in these settings. Over 80% wanted further training, particularly in behaviour and mental health management and communication. Training delivered in a preferred format that addresses the topics identified could improve the quality of care provided to adults on the autism spectrum and their healthcare experiences.